Ethics, Politics and Justice in Dante - Gaimari, Giulia; Keen, Catherine (UCL Press, 2019)
Ethics, Politics and Justice in Dante presents new research by international scholars on the themes of ethics, politics and justice in the works of Dante Alighieri, including chapters on Dante's modern 'afterlife'. Together the chapters explore how Dante's writings engage with the contemporary culture of medieval Florence and Italy, and how and why his political and moral thought still speaks compellingly to modern readers. The collection's contributors range across different disciplines and scholarly traditions - history, philology, classical reception, philosophy, theology - to scrutinise Dante's Divine Comedy and his other works in Italian and Latin, offering a multi-faceted approach to the evolution of Dante's political, ethical and legal thought throughout his writing career.